Evaluation of oral tranexamic acid as a novel treatment for melasma with a high benefit–risk ratio. (4th September 2022) - Simpson, Jordan; Peng, Lucy; Ting, William
Abstract: Background: Melasma is an acquired melanogenesis dysfunction resulting in chronic hyperpigmentation commonly affecting the face and other frequently sun‐exposed areas of the body. Melasma typically presents in women of reproductive age and can significantly impact self‐esteem, negatively affecting one's quality of life. In the United States, melasma is often treated with application of topical agents that interfere with melanin synthesis, lasers, or chemical peels; however, in some East Asian countries, oral tranexamic acid (TXA) is widely administered to alleviate hyperpigmentation during and after childbirth. TXA is currently only FDA‐approved to treat hypermenorrhea and reduce blood loss in surgery but may offer women in the United States an additional therapeutic option to treat melasma. Aims: The aim of this paper is to evaluate the safety and baseline efficacy of oral transmexic acid as a treatment for melasma. Methods: We retrospectively surveyed 42 patients of Fitzpatrick skin types III‐VI that were prescribed 650 mg of TXA ½ tablet to be taken twice daily by mouth. Results: We found majority of patients saw noticeable improvement in their melasma. Of the 42 patients, only seven experienced side effects. The side effects noted were headaches, malaise and nausea, gastrointestinal upset, congestion, numbness in legs, hypomenorrhea, and hypermenorrhea. Patients who experienced unpleasant side effects discontinued taking oral TXA and were relieved of their symptoms. No long‐term side effects were discovered, and the side effects experienced may be due to other confounding factors. Conclusion: From this data, we concluded oral TXA is a safe and effective treatment option for patients with persistent melasma.